Les seigneuresses de l'île - Barthe, Marcel (Les Argoulets, 2024)
Keywords: Congrégation de Notre-Dame; Femmes; Île-des-Soeurs

From Conversation to Contract: The Notary's Role in Nineteenth-Century Montreal - Olson, Sherry; Poutanen, Mary Anne (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Famille; Notaires

« Il s'en tuë jusques dans les jardins de Québec ». La place des animaux sauvages dans la ville (Québec et Montréal, 1663-1763) - Riguelle, William (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Alimentation; Faune

Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Robertine Barry, On l’appelait Monsieur - Desjardins, Sergine (Histoire Québec, 2024)
Keywords: Femmes; Journalistes; Patrie (La)

La Halte de La Visitation - Goulet, Patrick (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: La Visitation (église); Patrimoine; Sault-au-Récollet

Their benevolant design: conervative women and protestant child charities in Montreal - Harvey, Janice (McGill-Queen's University Press, 2024)
Keywords: Enfants; Femmes; Montreal Ladies' Benevolent Society; Protestants

Proprety and Power: Connecting the Dots - Olson, Sherry (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

Intimacies in the Neighbourhood: Revisiting Sex Commerce, Families, and Criminal Court Records in Early Nineteenth-Century Montreal - Poutanen, Mary Anne (Family and Justice in the Archives. Historical Perspectives on Intimacy and the Law, 2024)
Keywords: Criminalité; Famille; Femmes; Prostitution

La vie de John Elsdale Molson - Vailles, Alexis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Rosemont

La Maison Saint-Joseph. Témoin privilégié d'une oeuvre éducative - Drolet, Sylvie (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2023)
Keywords: Ahuntsic; Communautés religieuses; Jésuites; Saint-Joseph (maison)

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

La rue Saint-Denis (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Cherrier, Côme-Séraphin; Hôpital Sainte-Justine; Levasseur, Irma; Massicotte, Édouard-Zotique; Patrimoine; Plateau Mont-Royal (arrondissement); Saint-Denis (rue)

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

Historiennes engagées et femmes patriotes: la révolution de 1837-1838 et la place des femmes dans l'histoire du Québec - Arsenault, Mathieu (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Femmes; Histoire; Rébellions

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

Veuves et électrices : genre, citoyenneté et élection partielle à Montréal en 1832 - Bradbury, Bettina (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Élections

L’ancien cimetière Saint-Antoine (1799-1854) et son voisin rural à Pointe-aux-Trembles (1709-1843) : analyse comparative de la mortalité des enfants de deux populations du XIXe siècle sur l’île de Montréal - Duchemin, Emmanuelle (Université de Montréal, 2023)
Keywords: Enfants; Mortalité; Pointe-aux-Trembles; Saint-Antoine

L'école à Montréal: Un portrait en 1835 - Dufour, Andrée (Atlas historique du Québec. L'école au Québec, 2023)

DOHERTY, CHARLES JOSEPH - Glassford, Larry A. (Dictionnaire biographique du Canada, 2023)

La Faculté de médecine de l’Université de Montréal, 1843-2023: 180 ans à bâtir un avenir en santé - Goulet, Denis (Carte blanche, 2023)
Keywords: Médecine; Université de Montréal

« Le public a le droit d’être protégé contre un fléau mortel » : débat sur la quarantaine, la migration et la gouvernance libérale lors de l’épidémie de typhus de Montréal de 1847 - Horner, Dan (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Épidémies

LAMOTHE, MARGUERITE - Kirkland, Elizabeth (Dictionnaire biographique du Canada, 2023)

La British and Canadian School de Montréal - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)

Le High School of Montreal: fer de lance de l'enseignement anglo-protestant - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)
Keywords: Anglophones; High School of Montreal; Protestants

Les écoles des congrégations protestantes montréalaises - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)
Keywords: Protestants

Les initiatives privées de Montréal - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)
Keywords: Bute House (école protestante); Protestants

PHILLIPS, MARY MARTHA - McLeod, Ellen Easton (Dictionnaire biographique du Canada, 2023)

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

BRAININ, REUBEN - Orenstein, Eugene (Dictionnaire biographique du Canada, 2023)

Liens d’amitié, de parenté et d’appartenance à une collectivité : genre, itinérance et aide mutuelle à Montréal au début du XIXe siècle - Poutanen, Mary Anne (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Femmes; Itinérance

Évolution du sytème scolaire protestant de Montréal - Poutanen, Mary Anne; MacLeod, Roderick (Atlas historique du Québec. L'école au Québec, 2023)
Keywords: Protestants

Écrire la ville. Pouvoirs, urbanités et modernités dans l'espace québécois (XIXe-XXe siècles) - Robert, Camille; Ross, Daniel (Groupe d'histoire de Montréal, 2023)

MUIR, HENRIETTA LOUISE - Roome, Patricia (Dictionnaire biographique du Canada, 2023)

REXFORD, ELSON IRVING - Virr, Richard (Dictionnaire biographique du Canada, 2023)

Montréal, Heart of Indigenous Diplomacy - Arsenault, Mathieu (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Autochtones; Parlement

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

At St Anne's Market (1834-1844). All Kinds of Products, All Kinds of Meetings - Burgess, Joanne (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

L'intendance sociale du capital : philanthropie d'entreprise et hôpitaux généraux montréalais, 1880-1915 - Dubreuil, Anne-Marie (Université du Québec à Montréal, 2022)
Keywords: Hôpital Notre-Dame; Hôpitaux; Montreal General Hospital; Philanthropie; Royal Victoria Hospital

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Behind Strong Palings: Producing Knowledge in the Modern City at Montreal’s Emigrant Sheds, 1832-1852 - Horner, Dan (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Choléra; Épidémies

« Se soumettre de bon coeur à son mari »: le combat d'une femme face à l'autoritarisme marital - Lamonde, Yvan (Presses de l'Université Laval, 2022)
Keywords: Avocats; Doutre, Joseph; Femmes; Guibord, Joseph; Institut canadien; Mariage; Renaud, Marie-Zoé-Aimée; Trudel, François-Xavier-Anselme; Ultramontains

Éclairer et perfectionner l’esprit : l’éducation libérale et le délicat compromis entre raison et foi dans les écoles classiques de langue anglaise au Bas-Canada (1800-1840) - McCutcheon, Shawn (Études d'histoire religieuse, 2022)
Keywords: Langue; Libéralisme

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

Left Out of the Official History. The Women of St Anne's Market - Poutanen, Mary Anne; Olson, Sherry (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

CULLEN, MAURICE GALBRAITH - Prioul, Didier (Dictionnaire biographique du Canada, 2022)

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

Sir Hormisdas Laporte: Homme d'affaires et maire de Montréal (1850-1934) - Saint-Pierre, Marjolaine (Septentrion, 2022)
Keywords: Maires; Philanthropie

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

BLANCHARD, JULIE-MARGUERITE-LIA - Thifault, Marie-Claude (Dictionnaire biographique du Canada, 2022)

Découverte d'une voûte secrète datant de 1816 à l'église de La Visitation - Goulet, Patrick (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: La Visitation (église); Patrimoine; Églises

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Keywords: Famille; Logement; Mariage

The Goode House (The Westmount Historian, 2021)
Keywords: Conservation; Famille; Jardins; Patrimoine

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Quand le temps s'arrête: une promenade dans le jardin de la maison Goode / Window to the Past: A Walk in the Garden of the Goode House - Adib, Danièle; Crépeau, Antoine (The Westmount Historian, 2021)
Keywords: Jardins

L'homme aux 300 clochers - Anctil, Gabrielle (Continuité, 2021)
Keywords: Bourgeau, Victor; Églises

Montréal, haut lieu de la diplomatie autochtone - Arsenault, Mathieu (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Autochtones; Parlement

Three Generations of Goode Family - Breslaw, Caroline (The Westmount Historian, 2021)
Keywords: Famille

Au marché Sainte-Anne (1834-1844). Produits... et réunions de toutes sortes - Burgess, Joanne (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Alimentation; Boucherie; Marchands; Marchés; Sainte-Anne (marché)

BRAINERD, THOMAS CHALMERS - Cloutier, J.-Roger (Dictionnaire biographique du Canada, 2021)

Note de recherche. Les journaliers dans le district de Montréal en 1831 - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2021)
Keywords: Famille; Recensements; Travail

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

La tutelle des enfants mineurs au Bas-Canada: autorité domestique, traditions juridiques et masculinités - Garneau, Jean-Philippe (Revue d'histoire de l'Amérique française, 2021)
Keywords: Enfants; Famille; Femmes; Mariage; Veuvage

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Famille; Logement; Quartiers; Rosemont

Les rouges - Lamonde, Yvan; Livernois, Jonathan (Je me souviens, j'imagine: essais historiques et littéraires sur la culture québécoise, 2021)
Keywords: Bourget, Ignace; Communautés religieuses; Institut canadien; Papineau, Louis-Joseph; Partis politiques; Rouges; Rébellions

Albert Saint-Martin, militant d'avant-garde. Hochelaga 1865 – Faubourg Saint-Jacques 1947 - Larivière, Claude (Les Éditions de la Rue Dorion, 2021)
Keywords: Groupes populaires; Idéologies; Socialistes; Travail

DOUGALL, JOHN REDPATH - MacLeod, Roderick (Dictionnaire biographique du Canada, 2021)

Honnêtes hommes et gentilshommes : L'éducation classique des garçons et la formation du soi masculin au Bas-Canada à l’âge des révolutions (1791-1840) - McCutcheon, Shawn (Université McGill, 2021)
Keywords: Collèges classiques

HURLBATT, ETHEL - Morton, Suzanne (Dictionnaire biographique du Canada, 2021)

Un monument précurseur dans la définition d’une nouvelle identité architecturale dans le diocèse catholique romain de Montréal - Noppen, Luc (Journal of the Society for the Study of Architecture in Canada / Le journal de la Société d'étude pour l'architecture au Canada, 2021)
Keywords: Bourgeau, Victor; Sainte-Brigide (paroisse); Églises

LAFONTAINE, PIERRE-EUGÈNE - Normand, Sylvio (Dictionnaire biographique du Canada, 2021)

Une histoire sociale de la prostitution: Montréal, 1800-1850 - Poutanen, Mary Anne (Les éditions du remue-ménage, 2021)
Keywords: Femmes; Prostitution

Oubliées de l'histoire officielle. Les femmes du marché Sainte-Anne - Poutanen, Mary Anne; Olson, Sherry (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Femmes; Marchés; Sainte-Anne (marché); Travail

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman, William; Photographie; Écossais

GRAVEL, LUDGER - Roberts, David (Dictionnaire biographique du Canada, 2021)

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Synagogue Architecture in Canada: A Summary History - Stiefel, Barry L. (Journal of the Society for the Study of Architecture in Canada, 2021)
Keywords: Juifs

British Philanthropists and the Imperial Imagination or The Case of the Canadians Distressed by Fire at Montreal - Eamon, Michael (Canadian Historical Review, 2020)
Keywords: Britanniques; Incendies; Philanthropie

Le Plateau agricole (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
Keywords: Alimentation; Baron (côte à); Côtes; Institut des sourdes-muettes; Jardins; Meunerie; Plateau Mont-Royal

Women in Westmount (The Westmount Historian, 2020)
Keywords: Femmes; Peinture; Élections

CARLI, ALEXANDRE - Carlevaris, Anna Maria (Dictionnaire biographique du Canada, 2020)

Charivari, libéralisme et genre au Bas-Canada, 1820-1860 - Cournoyer, Amy (Université du Québec à Trois-Rivières, 2020)
Keywords: Femmes; Libéralisme

L’intimité française avec la " sauvagerie " à Montréal aux 17e-18e siècles - Deslandres, Dominique (Dix-huitième siècle, 2020)
Keywords: Autochtones; Criminalité; Délinquance; Français

GUYON, LOUIS - Dionne, Jean-Claude (Dictionnaire biographique du Canada, 2020)

Cohabitation, exploitation et nuisances à Montréal et à La Nouvelle-Orléans : les relations entre les populations urbaines et animales, 1840-1890 - Gagnon, Benjamin (Université du Québec à Trois-Rivières, 2020)
Keywords: Alimentation; Faune

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (Études d'histoire du Québec / Studies on the history of Quebec, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

GOLDSTEIN, MAXWELL - Lapidus, Steven (Dictionnaire biographique du Canada, 2020)

Eau courante, toilettes à eau et dernières latrines à Montréal, 1856-1915 - Lauzon, Gilles (Revue d'histoire de l'Amérique française, 2020)
Keywords: Aqueduc; Égouts

Du couvent des Dames du Sacré-Cœur à l’école secondaire Sophie-Barat. État des lieux d’une institution pionnière - M. Sénécal, Geneviève (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Keywords: Communautés religieuses

Le Club des archères de Montréal existait-il réellement? - Martin, Gabriel (Histoire Québec, 2020)
Keywords: Clubs; Femmes; Histoire; Montreal Ladies Archery Club / Montreal Archery Club

"Ils ne sont plus le peuple qu’ils étaient hier": la culture ouvrière à Montréal-Est au moment de la Confédération - Petitclerc, Martin; Bellavance, Claude; St-Hilaire, Marc (Le fait urbain, 2020)
Keywords: Cartier, Georges-Étienne; Lanctôt, Médéric; Montréal-Est; Partis politiques; Quartiers; Rouges; Saint-Jacques; Saint-Louis; Sainte-Marie; Travail; Élections

"Every Attention Will Be Paid to the Satisfaction of the Guests": Angélique Archambault and Donegana’s Hotel, 1852-1864 - Poutanen, Mary Anne (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Femmes; Hôtellerie; Mariage

The Perils of Sex Work in Montreal: Seeking Security and Justice in the Face of Violence, 1810–1842 - Poutanen, Mary Anne (The Violence of Work: New Essays in Canadian and US Labour History, 2020)
Keywords: Prostitution

Public Houses and Hidden Networks: Roles of Women in Mid-Nineteenth-Century Montreal - Poutanen, Mary Anne; Olson, Sherry (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Auberges; Famille; Femmes; Hôtellerie

Histoire des communautés noires au Québec et à Montréal (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Esclaves; Noirs

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

Andrew Fernando Holmes: Protestantism, Medicine, and Science in Nineteenth-Century Montreal - Vaudry, Richard W. (University of Toronto Press, 2020)
Keywords: Holmes, Andrew Fernando; Médecine; Protestants; Université McGill